Mammalian target of rapamycin regulates miRNA-1 and follistatin in skeletal myogenesis - Sun, Yuting (The Rockefeller University Press, 2010)
Mammalian target of rapamycin (mTOR) has emerged as a key regulator of skeletal muscle development by governing distinct stages of myogenesis, but the molecular pathways downstream of mTOR are not fully understood. In this study, we report that expression of the muscle-specific micro-RNA (miRNA) miR-1 is regulated by mTOR both in differentiating myoblasts and in mouse regenerating skeletal muscle. We have found that mTOR controls MyoD-dependent transcription of miR-1 through its upstream enhancer, most likely by regulating MyoD protein stability. Moreover, a functional pathway downstream of mTOR and miR-1 is delineated, in which miR-1 suppression of histone deacetylase 4 (HDAC4) results in production of follistatin and subsequent myocyte fusion. Collective evidence strongly suggests that follistatin is the long-sought mTOR-regulated fusion factor. In summary, our findings unravel for the first time a link between mTOR and miRNA biogenesis and identify an mTOR–miR-1–HDAC4–follistatin pathway that regulates myocyte fusion during myoblast differentiation in vitro and skeletal muscle regeneration in vivo.